1999
DOI: 10.1063/1.370891
|View full text |Cite
|
Sign up to set email alerts
|

Evolution process of cross-hatch patterns and reduction of surface roughness in (InAs)m(GaAs)n strained short-period superlattices and InGaAs alloy layers grown on GaAs

Abstract: Strain-dependent morphology of spontaneous lateral composition modulations in ( AlAs ) m ( InAs ) n shortperiod superlattices grown by molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
(19 reference statements)
2
21
0
Order By: Relevance
“…AFM measurements show that the CH pattern forms during the In y Ga 1Ày As growth, as reported in other studies of relaxed In y Ga 1Ày As epilayers grown on GaAs substrates [16]. The ridges are known to originate in the formation of misfit dislocations during the In y Ga 1Ày As growth [17] and the preferable striation along the ½1 % 1 0 direction has been attributed to the anisotropy in surface diffusion length of In atoms [18]. We find that the ridges are the most pronounced for the thin Ga 1Àx Mn x As epilayers and the surface becomes smoother for thicker epilayers.…”
supporting
confidence: 78%
“…AFM measurements show that the CH pattern forms during the In y Ga 1Ày As growth, as reported in other studies of relaxed In y Ga 1Ày As epilayers grown on GaAs substrates [16]. The ridges are known to originate in the formation of misfit dislocations during the In y Ga 1Ày As growth [17] and the preferable striation along the ½1 % 1 0 direction has been attributed to the anisotropy in surface diffusion length of In atoms [18]. We find that the ridges are the most pronounced for the thin Ga 1Àx Mn x As epilayers and the surface becomes smoother for thicker epilayers.…”
supporting
confidence: 78%
“…1a. This is typical of 2D growth of lattice-mismatched epilayer and is seen in various material systems, including GaAsP/GaP and SiGe/Si [11,12]. Upon closer inspection of the line scans along the [110]-and [1-10] directions in Figs.…”
mentioning
confidence: 70%
“…Figure 2 shows that the InAs QDs form highly ordered lines along ͗011͘ for a sample that was annealed for 60 min at 620°C prior to the deposition of InAs. As was predicted by Samonji et al 15 the surface of the sample has undulations that are parallel to ͓0-11͔ as well as less noticeable ones that are parallel to ͓011͔. It has been reported that, for InGaAs/GaAs heteroepitaxy, the incorporation rate of group III atoms to the B-type step, parallel to ͓011͔, is higher than that to the A-type step, parallel to ͓0-11͔.…”
Section: Resultsmentioning
confidence: 58%
“…It has been reported that, for InGaAs/GaAs heteroepitaxy, the incorporation rate of group III atoms to the B-type step, parallel to ͓011͔, is higher than that to the A-type step, parallel to ͓0-11͔. 15 This asymmetry in adatom diffusion, implying that the surface diffusion length along ͓011͔ is longer than that along the ͓0-11͔ direction, could explain the undulations observed. These undulations provide nucleation sites for the QDs, thus facilitating alignment of the QDs.…”
Section: Resultsmentioning
confidence: 94%